2020
DOI: 10.3389/fpsyt.2020.576367
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diabetes Induces Immune Dysfunction in Autistic Offspring Through Oxidative Stress in Hematopoietic Stem Cells

Abstract: Autism spectrum disorders (ASD) have been found to be associated with immune dysfunction and elevated cytokines, although the detailed mechanism remains unknown. In this study, we aim to investigate the potential mechanisms through a maternal diabetes-induced autistic mouse model. We found that maternal diabetes-induced autistic offspring have epigenetic changes on the superoxide dismutase 2 (SOD2) promoter with subsequent SOD2 suppression in both hematopoietic stem cells (HSC) and peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…This study has potential limitations for its clinical application due to limited cohort, while a power with n = 118 should be qualified to make a conclusion for RORA as an ASD biomarker, another much bigger clinical investigation is currently in our progress to establish a more accurate Pass/Fail Cut/Off value for ASD diagnosis. In addition, our results suggest that in the presence of prenatal exposure of risk factors (e.g., maternal diabetes) 22 , 25 , RORA expression is not only suppressed in neurons but is also suppressed in PBMC; this can be explained by the hypothesis that maternal diabetes-induced RORA suppression in hematopoietic stem cells during embryonic development can be inherited in PBMC as reported previously 39 . Furthermore, we have previously reported that prenatal hormone exposure, such as progestin and androgen 6 8 , 27 , is associated with ASD development 40 .…”
Section: Discussionsupporting
confidence: 83%
“…This study has potential limitations for its clinical application due to limited cohort, while a power with n = 118 should be qualified to make a conclusion for RORA as an ASD biomarker, another much bigger clinical investigation is currently in our progress to establish a more accurate Pass/Fail Cut/Off value for ASD diagnosis. In addition, our results suggest that in the presence of prenatal exposure of risk factors (e.g., maternal diabetes) 22 , 25 , RORA expression is not only suppressed in neurons but is also suppressed in PBMC; this can be explained by the hypothesis that maternal diabetes-induced RORA suppression in hematopoietic stem cells during embryonic development can be inherited in PBMC as reported previously 39 . Furthermore, we have previously reported that prenatal hormone exposure, such as progestin and androgen 6 8 , 27 , is associated with ASD development 40 .…”
Section: Discussionsupporting
confidence: 83%
“…We have previously found that maternal diabetes–mediated oxidative stress triggers epigenetic changes and gene suppression in both HSCs and PBMCs. PBMCs can inherit the similar properties from HSCs during differentiation after HSCT operation, and these properties may include epigenetic changes and subsequent gene suppression 25 . In this study, we showed that GFP lentivirus–infected HSCs from donor mice were found in PBMCs from recipient mice with ∼16.3% GFP + after HSCT; this further shows that HSCs can differentiate into PBMCs after HSCT, even though the number of transduced cells is relatively low.…”
Section: Discussionsupporting
confidence: 53%
“…We have previously reported that maternal diabetes induces epigenetic changes and gene suppression in neurons that, subsequently, contribute to autism‐like behaviors (ALBs) in offspring 4–6 . Furthermore, maternal diabetes–mediated epigenetic modifications in HSCs can be inherited by peripheral blood mononuclear cells (PBMCs) during differentiation, 24 subsequently inducing immune dysfunction in autism‐like offspring 25,26 . While HSC‐based therapeutic treatment has been shown to ameliorate ASD symptoms, 27,28 the underlying mechanism remains unclear and the strategy needs improvement 29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that hyperglycemia suppresses the expression of both OXT and OXTR, and OXTR expression remains low, while OXT expression returns to normal during subsequent normoglycemia. This effect can be completely reversed by SOD2 expression, indicating that hyperglycemia-induced OXTR suppression is due to hyperglycemia-induced consistent oxidative stress, which has been termed “hyperglycemia memory” ( El-Osta et al, 2008 ; Lu et al, 2020 ). Further investigation showed that hyperglycemia-induced OXTR suppression is due to oxidative stress-mediated consistent histone methylation on the OXTR promoter, indicating that these types of epigenetic changes can be inherited in offspring as a result of maternal diabetes.…”
Section: Discussionmentioning
confidence: 99%